Cutaneous infections by dematiaceous opportunistic fungi: Diagnosis and management in 11 solid organ transplant recipients. Issue 2 (17th October 2018) - Ferrándiz‐Pulido, Carla; Martin‐Gomez, M. Teresa; Repiso, Trinidad; Juárez‐Dobjanschi, Cecilia; Ferrer, Berta; López‐Lerma, Ingrid; Aparicio, Gloria; González‐Cruz, Carlos; Moreso, Francesc; Roman, Antonio; García‐Patos, Vicente
Summary: Background: The incidence of cutaneous infections by dematiaceous fungi is rising in our environment due to the high number of solid organ transplant recipients (SOTR). Objective: To review our experience in the management of cutaneous phaeohyphomycoses in a Spanish reference centre for dermatological care of SOTR. Methods: Retrospective clinical, histopathological and microbiological review of all SOTR diagnosed of a phaeohyphomycosis in a 7‐year period. Results: Eleven SOTR were identified (8 lung and 3 kidney). The lesions were solitary in six patients and multiple in five, affecting mostly the lower extremities. Early lesions showed epidermal hyperplasia and a diffuse dermal suppurative granulomatous infiltrate that was progressively substituted by fibrosis when the lesions were treated. Septated fungal structures with refractile walls were identified. DNA sequencing confirmed the presence of Alternaria spp (8 cases), Cladosporium cladosporioides, Microsphaeropsis arundinis and Exophiala oligosperma . Three patients with single lesions were treated with surgery, while the other 8 required long‐term antifungal therapy, including itraconazole, voriconazole and/or terbinafine, combined with surgery and reduction in tacrolimus doses. Conclusion: A clinical, histopathological and microbiological correlation is essential to corroborate this diagnosis. Solitary lesions are easily treated with surgery, but larger or multiple lesions may require long medical treatments combined with surgery and modification of immunosuppressive medication. The list of dematiaceous fungi implicated in cutaneous infections is expanding, in line with the availability of more sophisticated identification methods and the increasing number of immunosuppressed patients.